The evaluation of bacteriological quality parameters of natural spring water in Anatolian side of Istanbul Province - KAYHAN, FİGEN ESİN; SESAL, NÜZHET CENK (EGE UNIV, 2018)
The main purpose of this study was to investigate the bacteriological quality parameters of drinking fountains found in the Anatolian side of Istanbul on an annual basis (2014 year/12 month) and their evaluation in terms of human health. Samples were taken monthly from 10 different public drinking fountains for bacteriological analysis for a year in 2014. Bacteriological analysis were carried on using the membrane filtration technique; Coliform bacteria, Escherichia coli, Fecal coliform and Enterococcus counting. 95 samples were collected in total and bacteriological analysis performed on these showed that 46 % of the samples were drinkable and 49 % of them were not drinkable according to the national and international standards for drinking water quality. Additionally, 47,4 % of the samples had Coliform bacteria, 27,4 % had Enterococcus, 17,9 % had Escherichia coli and 14,7 % had Fecal coliform which showed that they were out of the standards. On the other hand, 48,4 % of the samples were compatible with the values indicated in the standards.
Keywords: Escherichia coli; Natural spring waters; Bacteriological analysis; CANADA; COLI